Enhanced scale inhibition against Ca3(PO4)2 and Fe2O3 in water using multi-functional fluorescently-tagged antibacterial scale inhibitors. Issue 4 (11th February 2020) - Zhang, Shaopeng; Jiang, Xin; Cheng, Shikun; Fu, Chang'e; Tian, Ziqi; Yang, Zhen; Yang, Weiben
Abstract : P-Free copolymers display enhanced scale (Ca3 (PO4 )2 and Fe2 O3 ) inhibition, improved antibacterial performance, and reliable in situ fluorescence detection of concentration. Abstract : Formation and deposition of scales, especially the refractory Ca3 (PO4 )2 and Fe2 O3, is an obstacle for water treatment and reuse. In situ concentration detection of P-free scale inhibitors also remains challenging. In this work, well-designed P-free copolymers, FM–AA–APEO with ternary units (acrylic acid (AA), allyl-polyethylene oxide (APEO), and fluorescent monomer (FM)), were employed as scale inhibitors against Ca3 (PO4 )2 and Fe2 O3 . The effects of ratios among different units were studied, and the optimized molar percentages of FM, AA, and APEO were 1.56%, 87.50%, and 10.94%, respectively. The optimized FM–AA–APEO exhibited much better scale inhibition (higher efficiency and lower dosage required) and antibacterial performance than commercial products. Fluorescence intensity and inhibitor concentration had good correlation ( R 2 > 0.99) regardless of the absence or presence of metal ions, providing a basis for in situ concentration detection. Scale inhibition mechanism investigations from micro- to macro-viewpoints demonstrated that the enhanced performance of FM–AA–APEO resulted from the synergistic effects of ternary compositions: AA units tightly bound metal atoms on small crystal particles via coordination and provided negative surface charges for electrostatic repulsion; APEO units with stretched hydrophilic sidechains contributed to steric repulsion among the particles; FM units not only exhibited designed in situ concentration determination ability (fluorescent groups in FM) and antibacterial effects (quaternary ammonium groups in FM), but also had unexpected strong coordination with Fe(iii ) atoms for strengthening Fe2 O3 scale inhibition. Understanding of the above mechanism provided more specific design strategies for the development and application of scale inhibitors in water.